If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -4(3x + 2y) = 0 17 + (3x * -4 + 2y * -4) = 0 17 + (-12x + -8y) = 0 Solving 17 + -12x + -8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -12x + -17 + -8y = 0 + -17 Reorder the terms: 17 + -17 + -12x + -8y = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -12x + -8y = 0 + -17 -12x + -8y = 0 + -17 Combine like terms: 0 + -17 = -17 -12x + -8y = -17 Add '8y' to each side of the equation. -12x + -8y + 8y = -17 + 8y Combine like terms: -8y + 8y = 0 -12x + 0 = -17 + 8y -12x = -17 + 8y Divide each side by '-12'. x = 1.416666667 + -0.6666666667y Simplifying x = 1.416666667 + -0.6666666667y
| -2Q^2+20Q-32=0 | | 3-t=6xa+21 | | b^3-8b^2-3b-4=0 | | X^2+4x+52= | | (1-p)x^2-4*p*x+4(1-p)=0 | | 4x+40=12x+5 | | f+16=-16 | | 7x+3-2(x+1)=9x+4 | | 0=x^2-2x-46 | | 2(y+2)=2 | | lnt=6 | | z+(13x+41)=180 | | x^3-2x^2-55x+160=0 | | 9x^4+x^2+8x+4=0 | | Z+(15x+37)=180 | | 5x-(2x+4)=6x-10 | | (15x+37)=(13x+41) | | 4000=60+32x | | 12x^4+17x^3+2x^2=0 | | 9+2z-4=8z+9-5z | | x=lne^6 | | 12x^4-17x^3+2x^2=0 | | (-5+6w+y)(-4)= | | z=(7x+43) | | 8x+12x=5 | | (-5+6+y)(-4)= | | 6/10=6/3 | | y=-0.5(-1)-1 | | 9+2z-4=8z-5z | | 19k+a=18l+9 | | (15x+49)+(7x+43)=180 | | y=-0.5(-2)-1 |